Exploring Knowledge, Attitudes, and Perceptions of Young Pharmacists on Telepharmacy Implementation – A Mini Review - Ghozali, Muhammad Thesa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Telepharmacy, a critical subset of telemedicine, has gained prominence as a transformative innovation addressing challenges in pharmaceutical care by enabling the remote delivery of services, including medication dispensing, patient counseling, and therapeutic monitoring. This narrative review investigates the state of telepharmacy in Indonesia, with a focus on the knowledge, attitudes, and perceptions of young pharmacists in the Special Region of Yogyakarta. The findings reveal significant knowledge gaps concerning telepharmacy tools and regulatory frameworks, which adversely influence pharmacists’ attitudes and perceptions. Although young pharmacists demonstrate higher technological proficiency and generally positive attitudes toward telepharmacy, hesitancy persists due to insufficient training opportunities and ambiguities in existing regulations. Telepharmacy offers substantial opportunities to bridge geographical barriers and enhance healthcare access, particularly in underserved and rural regions. However, its implementation is hindered by critical barriers, including regulatory gaps, inadequate technical infrastructure, and limited awareness among stakeholders. Drawing on successful telepharmacy models from the United States, Canada, and Australia, this review underscores the need for targeted educational initiatives, robust infrastructural investments, and regulatory reform to support telepharmacy adoption. Addressing these challenges will position telepharmacy as a vital tool in transforming Indonesia’s healthcare system, fostering equitable access, and advancing pharmaceutical care nationwide.